Failure in performance commitment and goodwill impairment: Evidence from M&As - Hongqi Yuan; Chong Gao; Haina Shi (China Journal of Accounting Studies (CJAS), 2020)
We examine whether and how the failure in performance commitment by an acquiree affects the acquirers' recognition of goodwill impairment. Based on a sample of A-share-listed firms during 2008-2016, we document the following evidence. First, both the likelihood and amounts of goodwill impairment increase significantly if an acquiree fails to meet the performance commitment. The results are robust to alternative measures of failed commitment and alternative sampling. Second, the relation is more pronounced (i) in the bear markets than in the bull markets, and (ii) for voluntary adoption of commitment terms than for mandatory ones. Third, the likelihood of goodwill impairment in the post-commitment period increases if an acquiree successfully met the commitment, especially if the acquiree met the commitment through earnings management. Last but not least, timely recognition of goodwill impairment for failed commitments leads to a reduction of future stock price crash risk.
Keywords: 650; M&A; performance commitment; goodwill impairment; earnings management; stock price crash risk